2008
DOI: 10.1182/blood-2007-12-130120
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide induces complete and partial remissions in patients with relapsed and refractory chronic lymphocytic leukemia

Abstract: This study investigated the activity of lenalidomide in patients with relapsed/ refractory chronic lymphocytic leukemia (CLL). Lenalidomide was given at 10 mg daily with dose escalation up to 25 mg daily. Three patients (7%) achieved a complete response (CR), one a nodular partial remission, and 10 patients a partial remission (PR), for an overall response (OR) rate of 32%. Treatment with lenalidomide was associated with an OR rate of 31% in patients with 11q or 17p deletion, of 24% in patients with unmutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
318
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(333 citation statements)
references
References 27 publications
10
318
2
3
Order By: Relevance
“…These results are in accordance with a recent study evaluating the use of lenalidomide in patients with CLL, which showed a response to treatment with immunomodulatory drugs (IMiDs) in high-risk patients with CLL. 22 Interestingly, in our study two out of four (50%) 17p-deleted refractory cases with CLL responded to thalidomide (reduction of WBC on day 7) as well as thalidomide/fludarabine therapy, suggesting that IMiDs may be effective in 17p-deleted patients with CLL. In addition, thalidomide/fludarabine therapy might also be considered in refractory patients with CLL.…”
Section: Discussionmentioning
confidence: 46%
“…These results are in accordance with a recent study evaluating the use of lenalidomide in patients with CLL, which showed a response to treatment with immunomodulatory drugs (IMiDs) in high-risk patients with CLL. 22 Interestingly, in our study two out of four (50%) 17p-deleted refractory cases with CLL responded to thalidomide (reduction of WBC on day 7) as well as thalidomide/fludarabine therapy, suggesting that IMiDs may be effective in 17p-deleted patients with CLL. In addition, thalidomide/fludarabine therapy might also be considered in refractory patients with CLL.…”
Section: Discussionmentioning
confidence: 46%
“…With its activity as a single agent or in combination, 11,15,[18][19][20][35][36][37][38] lenalidomide appears to be a strong candidate for inclusion in initial therapy of patients with aggressive Bcell non-Hodgkin's lymphoma. Furthermore, a recent study suggests that lenalidomide has improved activity in activated B-cell-like DLBCL compared with germinal center B-cell-like DLBCL.…”
Section: Ae N (%) Grade 1 Grade 2 Grade 3 Gradementioning
confidence: 99%
“…7 % of the patients achieved CR, 10 % PR. 31 % of the patients with 11q-or 17p-deletion (combined) responded, 24 % of the patients with unmutated IGHV and 25 % with fludarabine refractory disease [34]. A subgroup analysis of the trial showed that lenalidomide is also effective in patients with high-risk CLL (combined 11q-or 17p-deletion).…”
Section: Lenalidomidementioning
confidence: 99%